Wernicke encephalopathy and extrapontine myelinolysis in pregnancy with hyperemesis gravidarum: a double jeopardy - Verma, Divya; Kumar, Sanjeev; Thakur, Praveen; Shukla, Anurag; Gupta, Prateek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
We report a case of a pregnant woman who had been suffering from hyperemesis gravidarum presented with alteration of consciousness, nystagmus, generalized weakness and extrapyramidal symptoms at 16th week of gestation. Magnetic resonance imaging of the brain showed typical findings of Wernicke's encephalopathy and extrapontine myelinolysis. The clinical features responded dramatically to high dose thiamine supplementation. Wernicke encephalopathy should be diagnosed as early as possible to prevent long-term neurological sequela or death as well as fetal loss.